APPLICATION OF ASSET SECURITIZATION IN FINANCING AGRICULTURE IN SERBIA - Mirović, Vera; Bolesnikov, Dragana (Economics of Agriculture, 2013)
This paper aims to point out the possibilities of applying asset securitization in financing the Serbian agriculture. Government subsidies and banking loans do not provide sufficient funds so new sources of financing are in need. The process of asset securitization will enable the inflow of funds for agricultural loans approval as well as hedging. Agricultural loans can be used as collateral for issuing securities, although warehouse receipt, repurchase agreement and future income can also serve as collateral. Securitization can enable transfer of risk from insurance companies to financial market through CAT bonds and credit default swaps (CDS). The experience of countries having structured financing in agriculture is valuable for first steps in applying asset securitization in Serbia.